CD36 regulates macrophage and endothelial cell activation and multinucleate giant cell formation in anti neutrophil cytoplasm antibody vasculitis - Zhang, Xiang (Clinical immunology (Orlando, Fla.), 2024)
Copyright © 2024. Published by Elsevier Inc.